(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Technology is the application of knowledge to achieve practical goals in a reproducible way. The word technology can also mean the products resulting from such efforts, including both tangible tools such as utensils or machines and intangible ones such as software. Technology plays a critical role in science, engineering, and everyday life. A steam turbine with the case opened is an example of energy technology. Technological advancements have led to significant changes in society. The earliest known technology is the stone tool, used during prehistoric times, followed by the control of fire, which contributed to the growth of the human brain and the development of language during the Ice Age. The invention of the wheel in the Bronze Age allowed greater travel and the creation of more complex machines. More recent technological inventions, including the printing press, the telephone, and the Internet, have lowered barriers to communication and ushered in the knowledge economy. While technology contributes to economic development and improves human prosperity, it can also have negative impacts like pollution or resource depletion or may cause social harms like technological unemployment resulting from automation. As a result, there are ongoing philosophical and political debates about the role and use of technology, the ethics of technology, and ways to mitigate potential downsides. Based on the overall result, the descriptive method obtained an average of 3.23, 3.07, and 3.2, which means. Technology helps Paradise employees in providing and maintaining high standards. According to the general result based on the employees of Paradise Hotel, technology has been a great help for them to accomplish not lowering the standard rate of their hotel but increasing it even more.